ANALISIS KEPERILAKUAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR DALAM PERSPEKTIF TEORI PERILAKU TERENCANA DI KANTOR SAMSAT GIANYAR - Ni Made Wisni Arie Pramuki; Ni Ketut Wanadri (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to analyze the payment behavior of taxpayers in the perspective of behavioral planning theory. This research was conducted at the Gianyar Regency Samsat office. The total population in this study was 346.285 by taking a sample of 100 taxpayers who were respondents in this study using Slovin's theory with an error rate of 10%. The data analysis method used is SEM PLS with the help of Smart PLS software. The results of the study indicate that attitudes, subjective norms and perceived behavioral control have a positive and significant effect on taxpayers' intentions in paying taxes. Another finding in this study is that the direct influence of perceived behavioral control has a positive and insignificant effect on the behavior of taxpayers to pay taxes. Another finding is that direct perceived behavioral control is not able to increase the behavior of taxpayers to pay motor vehicle taxes, but through intention, it is able to influence taxpayers to pay motor vehicle taxes. So the behavior of the taxpayer is very dependent on the intention of the taxpayer to pay the motor vehicle tax